The impact of AI on algorithm design innovations and practical applications - Ma, Xiangbo (Edelweiss Applied Science and Technology, 2025)
Artificial intelligence (AI) has greatly influenced the innovation and practical application of algorithm design. With the rapid development of AI technology, the traditional algorithm design paradigm is undergoing profound changes. AI leverages machine and deep learning to automate algorithm optimization and adaptation for tasks and environments. This involves selecting suitable models and preparing specific datasets for training and validation. It also includes implementing complex algorithms for automatic optimization, allowing models to learn and improve over time with minimal manual intervention. AI-driven innovation not only improves the efficiency and accuracy of algorithm design but also expands its range of practical applications in multiple fields. This paper summarizes evaluation criteria and efficiency indicators for AI-driven algorithms, discusses their basic principles, and examines real-world applications to predict future trends and potential uses, thereby facilitating innovative applications of deep learning technology. AI integration in algorithm design has advanced healthcare, finance, and autonomous driving. It automates optimization, enabling rapid algorithm improvement and enhancing decision-making and efficiency. AI-driven algorithms adapt to changes, ensuring long-term relevance and effectiveness.